Programmed innovation in team sport using needs driven innovation - Ringuet-Riot, C.; Carter, S.; James, D. A. (Procedia Engineering, 2014)
Innovation is nothing new to sport, but represents everything that is `new` and adopted to facilitate a competitive advantage. In the sport context, innovations that are solutions to a pre-identified problem or need are critical to developing sport and for maximising the experiences and performances of individuals and organisations. Advances in sport technology are part of the growing global sports and recreation industry, and at the individual level, technology innovation is changing the way that we practice and connect with sport. In this paper, we apply a model for programmed innovation in sport to an elite sport setting with a particular focus on team sports. Using a qualitative methodology we explore the perceptions of key stakeholders (such as sport managers, coaches, athletes, and science and engineering researchers) to investigate needs for technology innovation. The results demonstrate areas of key opportunity for technology innovation in the research and commercialisation context.